Immunogenicity and safety of an investigational hepatitis B vaccine with a Toll-like receptor 9 agonist adjuvant (HBsAg-1018) compared with a licensed hepatitis B vaccine in patients with chronic kidney disease and type 2 diabetes mellitus. Issue 7 (11th February 2015) - Janssen, Julia M.; Heyward, William L.; Martin, J. Tyler; Janssen, Robert S.
Highlights: Phase 3 trial of investigational hepatitis B vaccine in CKD and diabetes. HBsAg-1018 induced superior seroprotection to HBsAg-Eng. The safety profile of HBsAg-1018 was similar to that of HBsAg-Eng. Abstract: Background: Many patients with chronic kidney disease (CKD) are hyporesponsive to currently licensed alum-adjuvanted hepatitis B vaccines, including Engerix-B ® (HBsAg-Eng). Seroprotection rates (SPRs) are further reduced in CKD patients with diabetes mellitus. Three doses of an investigational hepatitis B vaccine (HBsAg-1018) that uses a Toll-like receptor 9 agonist demonstrated superior SPRs to 4 double doses of HBsAg-Eng in a large phase 3 trial of CKD patients. Methods: A prespecified subgroup analysis of immunogenicity was conducted in CKD participants with type 2 diabetes in the phase 3 trial. Results: In 328 participants, the peak SPR in the HBsAg-1018 group met criteria for noninferiority and superiority to the peak SPR in the HBsAg-Eng group. The peak geometric mean concentration of antibody against hepatitis B surface antigen in the HBsAg-1018 group was statistically significantly higher than in the HBsAg-Eng group. Conclusion: HBsAg-1018 induced significantly higher seroprotection than HBsAg-Eng in CKD patients with diabetes.